Botanical Field Notes from Rajasthan with Records of New Plant Species - Sharma, Satish Kumar; Sarsavan, Anil (International Journal of Scientific Research in Biological Sciences, 2024)
This study explores the flora of Rajasthan, India, with a specific focus on documenting the species records new to flora of Rajasthan and the naturalization of some garden species in the wild. We identified several species exhibiting the phenomenon of naturalization, including Iochroma arborescens, Dysphania pumilio, Opuntia cylindrica, Cyperus alternifolius and Alternanthera philoxeroides. These five species are new also to the flora of Rajasthan. Additionally, the naturalization of cultivated species like Dodonaea angustifolia, Nerium oleander, and Tithonia diversifolia is also documented. The findings highlight the importance of continuous monitoring and updating of flora to reflect changes in the plant composition of a region. The study also reports interesting plant species occurrence in the gorges of Shahabad Tehsil area in Baran District which were earlier not reported for this region. New locations of occurrence of Borassus flabellifer is also listed in the present paper.